Analyzing Translation Techniques in Edgar Allan Poe’s The Tell-Tale Heart - AGES MELINDA SARI; EVERT HARYANTO HILMAN (Universitas Negeri Semarang, 2026)
This study aims to identify and analyze the techniques of translation employed in the Indonesian translation of Edgar Allan Poe’s short story The Tell-Tale Heart. Using a descriptive qualitative method with purposive sampling mainly focuses on four related techniques: amplification, reduction, established equivalent, and variation; the research mainly studies how the translator translated the short story from the source language to the target language. The research bases its study on Molina and Albir’s theory of techniques of translation, which provides a comprehensive and systematic framework for analyzing translation choices. The findings indicate that four translation techniques are applied in the research, including reduction (30.30%), established equivalent (9.09%), amplification (45.45%), and variation (15.50%). Out of the 33 data samples examined, amplification is the most frequently used technique (45.45%), suggesting the translator’s attempt to provide additional contextual information to enhance comprehension for target readers. In contrast, the established equivalent technique appears least frequently (9.09%). This research may contribute to the subject of literature translation by demonstrating that understanding the standard grammar of the target language may help the translator in translating a literary work better to prevent mistranslation or loss of information during the translation process.